System for disease development prediction using time series medical image data analysis - MOON SEUNG DAE; KIM SUNG WOO (2022)
The present invention relates to a disease development prediction system through time-series medical image data analysis. According to the present invention, the disease development prediction system through time-series medical image data analysis includes: an image data input unit that receives time-series medical image data of a subject whose development of a disease is to be predicted; an image pre-processing unit that analyzes the time-series medical image data and extracts feature data that can be classified as a disease; and a prediction unit that predicts a stage of a disease by inputting the time-series medical image data and feature data to a machine learning model that has been trained. According to the present invention, by analyzing a large amount of time-series medical image data to predict disease development information, it is possible to improve the accuracy and reliability of prediction results. By constructing a predictive model to comprehensively consider time and feature weights of time-series medical image data, accuracy and reliability of prediction results can be improved. 본 발명은 시계열 의료 영상 데이터 분석을 통한 질환 발달 예측 시스템에 관한 것이다. 본 발명에 따르면, 시계열 의료 영상 데이터 분석을 통한 질환 발달 예측 시스템은 질환 발달을 예측하고자 하는 피검자의 시계열 의료 영상 데이터를 입력받는 영상 데이터 입력부, 상기 시계열 의료 영상데이터를 분석하여, 질환으로 분류할 수 있는 특징 데이터를 추출하는 영상 전처리부, 그리고 상기 시계열 의료 영상 데이터 및 특징 데이터를 학습이 완료된 기계 학습 모델에 입력하여 질환의 단계를 예측하는 예측부를 포함한다. 이와 같이 본 발명에 따르면, 대량의 시계열 의료 영상 데이터를 분석하여 질환의 발달정보를 예측함으로써, 예측 결과의 정확성 및 신뢰성을 향상시킬 수 있고, 시계열 의료 영상 데이터의 시간 및 특징에 관한 가중치들을 종합적으로 고려하도록 예측 모델을 구축함으로써, 예측 결과의 정확성 및 신뢰성을 향상시킬 수 있다.